KEBIJAKAN DINAS SOSIAL DALAM MENGATASI MASALAH GELANDANGAN DAN PENGEMIS DI KOTA PALANGKA RAYA - Devi Christy; Jovano Deivid Oleyver Palenewen (Jurusan Ilmu Pemerintahan, 2021)
The problem of social welfare is a homework that has not been resolved by either the central government or local governments, especially the homeless and beggars. This study aims to examine the phenomenon of homeless and beggars in Palangka Raya City? and what are the efforts made by the Social Service in dealing with homeless people and beggars in Palangka Raya City?. The research method used is descriptive qualitative research. Sources of data used are primary data and secondary data. Data collection techniques used are observation, interview and documentation techniques. The data analysis techniques used according to Miles and Humberman include data collection, data reduction, data presentation and drawing conclusions. The results of the study concluded that the phenomenon of vagrants and beggars in Palangka Raya City was caused by two factors, namely the poverty factor and the laziness of the individual concerned. The policy efforts of the Palangka Raya City Social Service in dealing with homeless and beggars in accordance with Regional Regulation Number 09 of 2012 are by carrying out three efforts, including (1) preventive efforts, namely the implementation of counseling activities, as well as skills training to the general public, (2) responsive efforts namely carrying out routine patrols, (3) rehabilitative efforts, namely sheltering homeless people and beggars who were netted in raids, sponsorship, and returning to their respective areas but still being monitored.